DEVELOPING CRITICAL THINKING SKILLS THROUGH ENGLISH READING ACTIVITIES IN SECONDARY SCHOOLS IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the development of critical thinking skills through English reading activities in secondary schools in Uzbekistan. In an era where global interconnectedness and information literacy are increasingly vital, fostering critical thinking is essential for students' academic and personal growth. While the Uzbek educational system has embraced reforms focused on learner-centered methodologies, challenges persist in integrating critical thinking into classroom practices. The article explores how English reading lessons, if designed thoughtfully, can serve as a powerful tool for developing critical thinking. By engaging with texts beyond surface comprehension, students can learn to analyze, evaluate, and reflect on the information presented. It emphasizes the role of teachers in creating a classroom environment conducive to inquiry and reflection. Furthermore, the article proposes effective strategies for educators, including open-ended discussions, debates, and comparative analyses, aimed at fostering a more reflective and analytical approach to learning. This research offers practical insights for improving English language instruction and student cognitive engagement in Uzbekistan.